An Estimate of Income and Employment Generated through Forestry Sector in Chandrapur District of Maharashtra State - Chowdhary, R. L. (Indian Forester, 1975)
This paper highlights the contribution of 4 main activities of forestry sector, namely, forest management, harvesting, primary manufacturing industries and secondary manufacturing industries, to the production and employment potential of Chandrapur district of Maharashtra State. Production of timber and fuel in the district amounted to roughly 23.47% and 19.01 % of the total state production and nearly 4.1% of the jobs in 1970-71 in the district. The income generated in the form of wages and salaries in the same year was Rs. 4,34,32,905/-. Result of such a large consumer spending has stimulated the economy of the district considerably. Larger investments in forestry sector, particularly in the forest management and harvesting activities, can promote further growth and development in other sectors of the economy of the district.